Pola Kebijakan Digitalisasi Penyiaran di Indonesia - Assyari Abdullah (ARISTO, 2020)
The purpose of the study is to see how broadcasting digitalization policies in Indonesia after the shaking of the status of broadcast digitalization after the Supreme Court's decision. This research uses a qualitative descriptive method with a case study approach to explore the issues and problems that exist around the digitalization of broadcasting in Indonesia. The practice of broadcasting digitalization in Indonesia does not have clear regulations after Ministerial Regulation 22/2011 has been revoked. So that policies and regulations in managing broadcast digitalization are unclear. Simulcast Public Broadcasting Institutions (LPPs) and Private Broadcasting Institutions (LPS) have conducted trials in the field of broadcast digitalization. TVRI as a Public Broadcasting Institution (LPP) already has TVRI Digital Broadcasting Channel -1, TVRI Digital Broadcast -2, TVRI Digital Broadcast -3, TVRI Digital Broadcast -4 and TVRI Digital-HD Broadcasting. Private Broadcasting Institutions (LPS) that conduct trials are Nusantara TV, Inspira TV, Kompas TV, Gramedia TV, Tempo TV, Net TV, CNN TV, Muhammadiyah TV, Merahputih TV, Badar TV, and Persada TV. The government and all stakeholders must seriously oversee the revision of the broadcasting law that accommodates broadcast digitalization.